GE_GERICHTE P/23473/2015 vom 28. April 2016 - GE Cour de justice (2016)
BRIGANDAGE; SÉJOUR ILLÉGAL; FIXATION DE LA PEINE; APPRÉCIATION DES PREUVES; RÉCIDIVE(INFRACTION); RÉVOCATION DU SURSIS | CP.140.1.1; CP.47; CP.49.1; CP.42.2; CP.46.1; LEtr.115.1.b